The Russian version of the Abbreviated Math Anxiety Scale: psychometric properties in adolescents aged 13–16 years - Marakshina, Julia; Pavlova, Anna; Ismatullina, Victoria; Adamovich, Timofey; Mironets, Sofia; Sitnikova, Maria A.; Lobaskova, Marina; Malykh, Sergey (Frontiers in Psychology, 2023)
This study is the first to assess the internal consistency and factor validity of the Abbreviated Math Anxiety Scale (AMAS) in a sample of Russian adolescents as well as gender differences and gender invariance. The study included 4,218 adolescents in grades 7–9 (M = 14.23, SD = 0.92). Internal consistency, measured with Cronbach’s alpha, was high. Analysis of the factor structure revealed the best correspondence of the second-order factor model, which included two scales (learning math anxiety and math evaluation anxiety) and the general scale of math anxiety. There were greater gender differences in the all three scales. Analysis of gender invariance demonstrated that the mathematics anxiety construct was uniform in boys and girls. These findings confirm the reliable psychometric properties and validity of the AMAS, enabling its use in adolescents.